2017
DOI: 10.1038/ja.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of indole core-based derivatives with potent antibacterial activity against resistant bacterial pathogens

Abstract: The emergence of drug resistance in bacterial pathogens is a growing clinical problem that poses difficult challenges in patient management. To exacerbate this problem, there is currently a serious lack of antibacterial agents that are designed to target extremely drug-resistant bacterial strains. Here we describe the design, synthesis and antibacterial testing of a series of 40 novel indole core derivatives, which are predicated by molecular modeling to be potential glycosyltransferase inhibitors. Twenty of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The indole–imidazoline hybrids 30 (MIC: 6.25 to >100 μg/ml) and 31 (MIC: 6.25 to >100 μg/ml) showed considerable activity against S. aureus and MRSA, whereas hybrids 32 (MIC: ≥640 μg/ml) were devoid of activity, suggesting that the hydrazone linker between indole and imidazoline moieties had a great influence on the activity. [ 75,76 ] In particular, hybrids 30a,b (MIC: 3.13–25 μg/ml) possessed a broad‐spectrum activity against S. aureus , S. saprophyticus , S. pyogenes , S. pneumonia , C. urealyticum , MSSA ATCC‐25923, MSSA (clinical isolate), VRE, multidrug‐resistant A. baumanii , MRSA ATCC‐S‐6007, and eight MRSA clinical isolates. [ 75 ] Thus, these two hybrids were promising candidates for the development of broad‐spectrum anti‐infective agents.…”
Section: Indole/isatin–azole Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…The indole–imidazoline hybrids 30 (MIC: 6.25 to >100 μg/ml) and 31 (MIC: 6.25 to >100 μg/ml) showed considerable activity against S. aureus and MRSA, whereas hybrids 32 (MIC: ≥640 μg/ml) were devoid of activity, suggesting that the hydrazone linker between indole and imidazoline moieties had a great influence on the activity. [ 75,76 ] In particular, hybrids 30a,b (MIC: 3.13–25 μg/ml) possessed a broad‐spectrum activity against S. aureus , S. saprophyticus , S. pyogenes , S. pneumonia , C. urealyticum , MSSA ATCC‐25923, MSSA (clinical isolate), VRE, multidrug‐resistant A. baumanii , MRSA ATCC‐S‐6007, and eight MRSA clinical isolates. [ 75 ] Thus, these two hybrids were promising candidates for the development of broad‐spectrum anti‐infective agents.…”
Section: Indole/isatin–azole Hybridsmentioning
confidence: 99%
“…[ 75,76 ] In particular, hybrids 30a,b (MIC: 3.13–25 μg/ml) possessed a broad‐spectrum activity against S. aureus , S. saprophyticus , S. pyogenes , S. pneumonia , C. urealyticum , MSSA ATCC‐25923, MSSA (clinical isolate), VRE, multidrug‐resistant A. baumanii , MRSA ATCC‐S‐6007, and eight MRSA clinical isolates. [ 75 ] Thus, these two hybrids were promising candidates for the development of broad‐spectrum anti‐infective agents.…”
Section: Indole/isatin–azole Hybridsmentioning
confidence: 99%
“…The anti‐MRSA SAR of indole–guanidine hybrids 57 (MIC: 3.12 to >100 µg/ml) and 58 (MIC: 3.12 to >100 µg/ml) indicated that the C‐5 position of indole moiety was more favorable for modification than the C‐6 position, and the chloro group at the para position of the phenyl ring was highly preferred. [ 93 ] Among them, hybrids 57a (MIC: 3.12–12.5 µg/ml) and 58a (MIC: 6.25–12.5 µg/ml) possessed a considerable activity against various Gram‐positive pathogens, including MRSA ATCC‐S‐6007, MRSA (clinical isolate), MSSA ATCC‐25923, MSSA (clinical isolate), VRE, S. saprophyticus , S. pyogenes , and S. pneumoniae , and the molecular modeling predicated that these hybrids were potential glycosyltransferase inhibitors.…”
Section: Indole Hybridsmentioning
confidence: 99%
“…The anti-MRSA SAR of indole-guanidine hybrids 57 (MIC: 3.12 to >100 µg/ml) and 58 (MIC: 3.12 to >100 µg/ml) indicated that the C-5 position of indole moiety was more favorable for modification than the C-6 position, and the chloro group at the para position of the phenyl ring was highly preferred. [93] Among them, hybrids 57a (MIC: pneumoniae, and the molecular modeling predicated that these hybrids were potential glycosyltransferase inhibitors.…”
Section: F I G U R Ementioning
confidence: 99%
“…Indole scaffold represents an interesting class of biologically active heterocyclic compounds. The scaffold possesses diverse biological activities including anti-inflammatory (1), anticonvulsant (2), antidepressant (3), antiallergic (4), antitubercular (5), antidiabetic (6), antiviral (7) and antimicrobial activity (8)(9)(10)(11). Oxindole and other related ring systems also exhibit several biological activities (12)(13)(14)(15).…”
mentioning
confidence: 99%